PENGARUH LATAR BELAKANG PENDIDIKAN, PENGETAHUAN BIOGAS, STATUS EKONOMI KELUARGA, MELALUI SIKAP TERHADAP PENGELOLAAN BIOGAS DI DESA BERPREDIKAT MANDIRI ENERGI KABUPATEN MALANG SERTA IMPLEMENTASINYA BAGI PENGELOLA BIOGAS - Hilda Ernani (Bioscientist : Jurnal Ilmiah Biologi, 2015)
The objectives of this study are as follows: 1) describe the conditions of educational background, biogas knowledge, family economic status, attitude and management of biogas in villages with energy independent titles in Malang Regency, 2) explain the relationship between exogenous variables of educational background, biogas knowledge, and family economic status in the management of biogas in the village with the independent energy title of Malang Regency, 3) explaining the influence of educational background, biogas knowledge, and family economic status on the attitude of the community in the energy independent Malang Regency, 4) explaining the influence of educational background, knowledge biogas, family economic status, and attitudes towards biogas management in villages predicated on energy independence in Malang Regency, and 5) implementing research results in the form of booklets for learning biogas management communities in Malang Regency. The instrument for measuring the educational background of farmers is expressed based on the length of time passed by farmers in taking education. The instrument for measuring biogas knowledge is a test of knowledge about biogas management. The instrument used to measure family economic status is an economy class index based on ownership of valuables. The instrument used to measure attitudes is a test of attitude towards biogas management. The instrument for measuring behavior related to the management of biogas is a matter of observation and structured interviews. Instruments for collecting data first by compiling a grid, which includes empirical indicators, descriptors of empirical indicators, and questions. Causal correlational research results show: 1) educational background, biogas knowledge, and family economic status towards attitudes accepted at a significant level p = 0.007 <0.05, terminated coefficient values R2 = 0.124 can be interpreted as educational background, knowledge of biogas together the same effect on attitudes is 12.4%, meaning that other variables also influence attitudes as much as 87.6% and cannot be explained in this research. Individual education background influences attitudes of 10.1%, while knowledge variables and family economic status individually do not influence attitudes. 2) educational background, biogas knowledge, family economic status, and joint attitudes influence the management of biogas. The terminated coefficient value R2 = 0.175 can be interpreted that the educational background, biogas knowledge, family economic status, and attitude together influence the management of biogas by 17.5%, meaning that other variables also influence the management of biogas by 82.5% and can not be explained in this study. Individual economic status influences the management of biogas by 25.4% and individual attitudes influence the management of biogas by 34.2%. And 3) there is an indirect influence of educational background through attitudes towards biogas management and no indirect influence on biogas knowledge, family economic status through attitudes towards biogas management. The results of the development research, namely the analysis of data from Booklet validation results by content expert validators and learning media experts. The results of content expert validation, that Booklet is in a very good category and does not need to be revised with a total value of 96.65%. Validator in the field of learning media gives a decision that Booklet is in a good category and does not need to be revised with a total value of 80.93%. From the results of the decision by the validator team, it can be concluded that it does not need to be revised again and can be used.